Estudo morfo-anatômico, fitoquímico e Bioprospecção de atividade antibacteriana, sinergismo e de Toxicidade das partes aéreas de Scoparia dulcis L. - FERREIRA, Jouberth Vieira (2023)
Scoparia dulcis L. (Plantaginaceae) is a widely propagated medicinal plant, commonly found in urban environments and popularly known as "vassourinha" or "vassourinha-doce." It is extensively used in folk medicine for the treatment of bacterial infectious processes, but its identification is prone to errors due to its close resemblance to other plants. In this context, emphasizing the need for morpho-anatomical, phytochemical, and bioprospecting studies on the biological effects of this species is crucial to validate its therapeutic use, ensuring efficacy, safety, and quality parameters. The aim of this work was to provide macro and microscopic identification parameters of the plant material, detect the major classes of secondary metabolites, and conduct a bioprospecting study on the antibacterial activity and toxicity of the aerial parts of S. dulcis. The plant material was collected in São Luís municipality during the morning of March 2023, and the exsiccata is deposited in the Herbarium of the Federal University of Maranhão/MAR-UFMA. Morphological parameters, including stem and leaf characteristics, were analyzed using unaided-eye observation and a stereomicroscope, following literature descriptions. For anatomical description, cross-sections of the stem and leaves were examined under an optical microscope. The extract from aerial parts was obtained by maceration for 7 days with 70% ethanol and a 1:10 hydro module. Phytochemical screening was employed for metabolite class analysis. Antibacterial tests were conducted using agar diffusion and microdilution against Gram-positive and Gram-negative microorganisms, including synergy testing with standard antibiotics. Toxicity was assessed through hemolysis tests and bioassays with Tenebrio molitor larvae. The morphological study revealed that the stem has a green color, is flexible, and has an angular shape, while the leaves are lanceolate, with an obtuse apex and cuneate base, and concolorous green. The presence of glandular trichomes and Caspary stripes on the stem enhances authenticity. The extract exhibited the presence of alkaloids, saponins, steroids, tannins, and flavonoids. Microbiological tests demonstrated antibacterial activity, notably against Pseudomonas aeruginosa with an inhibition halo ranging from 1.43 to 1.56 cm and a minimum inhibitory concentration (MIC) of 200 mg/mL, and Klebsiella pneumoniae with an MIC of 100 mg/mL. However, no significant synergy with antibiotics was observed. Toxicity tests revealed low activity with no statistically significant differences in survival rates among different concentrations in the T. molitor test. Additionally, the hemolysis test determined an Effective Concentration for 50% hemolysis (EC50) of 326.90 ± 0.00238 mg/mL. Morpho-anatomical analyses of S. dulcis leaves and stem facilitated the characterization of the plant material, providing support for its correct identification and differentiation from similar species. Bioprospecting demonstrated the predominance of phenolic substances in the hydroalcoholic extract and the potential of the plant species for the development of antibacterial products.